Mentalization mediates the relationship between early maltreatment and potential for violence in adolescence - Taubner, Svenja; Zimmermann, Laura; Ramberg, Axel; Schröder-Pfeifer, Paul (Psychopathology, 2016)
Aim: The present study investigates the role of attachment representation and mentalization as possibly protective factors in the relationship between early maltreatment and potential for violence in adolescence. Methods: For the current study, 161 adolescents, aged 14-21 years, were recruited from high schools and youth psychiatry. Early maltreatment was assessed by the Childhood Experiences of Care and Abuse Questionnaire, attachment was assessed using the Adult Attachment Projective Picture System, and mentalization was coded with the Reflective Functioning Scale from Adult Attachment Interviews. Potential for violence was operationalized using the Reactive-Proactive Aggression Questionnaire, and the presence of conduct disorder was assessed by the Structured Clinical Interview. Using structural equation modeling, reflective functioning and attachment were tested as mediators on the direct effect of early maltreatment on potential for violence. Results: There was a direct effect of early maltreatment on potential for violence. Furthermore, this direct effect was partially mediated by reflective functioning but not by attachment representations. Discussion: The results contribute to the idea that mentalization serves as a protective factor that may suspend the pathway from early maltreatment to violence in adolescence. Because of the transformation of attachment patterns into generalized cognitive models of attachment, attachment in adolescence may have a less pronounced effect on violence in this specific developmental phase. Future studies should test for further group differences in community and clinical groups, which was not possible in the present study due to the limited sample size.
Gesehen am 20.05.2020